KEJAHATAN MONEY LAUNDERING DALAM PEMILUKADA (RE-ORIENTASI DAN RE-EVALUASI NILAI TERHADAP KEBIJAKAN PELAKSANAAN PEMILUKADA) - M. Arief Amrullah (Jurnal Cakrawala Hukum, 2013)
Money laundering was a sequel crime. It meant that it was a medium from any kinds of crimes included inorganized crime to blur the origin of wealth. The medium for the hiding process was through either bank or nonbank as what people always said so far. However, it could develop in financing Pemilukada as the first start.Next, if the candidate of the supported district head won, money laundering could be done in any kinds ofprojects. It was a crime. By evaluating the policy in Pemilukada implementation, it was hoped that it couldclose the chance for certain parties to exploit Pemilukada as one of the mediums or means for money laundering.Various efforts were done by making standards carried out by the global elites. Thus, the policy must havebeen brave to loose or even release the knots which were packed in standard form that so far had given potentialto money laundering. Finally, to reach the success in preventing and wiping out money laundering, as it waswritten in regulation no 8 year 2010, it had to be supported by other policies, including in this case the policyin Pemilukada management. Criminal law did not stand alone in the effort to prevent and wipe out moneylaundering.